PENGEMBANGAN BAHAN AJAR BAHASA ARAB BERBASIS MULTIMEDIA INTERAKTIF KELAS V - Melani Albar (Universitas Islam Darul 'Ulum Lamongan, 2019)
Abstract Language remains important tools for daily life and usage, mainly in communication. In relation of it, A good communication requires such vocabulary expansion. Vocabulary literally know as Mufradat about which people have high intention of its understanding and large acquisition while the intention do not come together with the main way to understand through memorizing, effectively. Concern to its problem, researches wants to develop teaching materials about vocabulary memorizng through music tegether with its sign and pictures in purpose of showing easiest way of memorizing. The result of the study shows that teaching media of arabic language using multimedia interactive has shown high effectivity and attractiveness. It can be proved from students anthusiasm and atrractiveness of learning its vocabulary. Result of ‘t’ test of pre test shows in the average of mean about 59,58 of experiment group while control group having its average about 42,83. From its score there are no high range of different of its score but ekspriment group having high score that the control one. In continued of its appliances, the researcher continued to give an application of interactive multimedia to eksperiment group and convensional for control group. Finding result of it, the post test given three times and it had shown the average of 82,00, followed by the second about 82.33, and it has shown the improvement about 0.33 while the rest shown average point about 81.67. From the average above, it can be conclude that the use of interactive multimedia has brought students in high and esiest way of understandin and memorizing, and it can be also concluded that the use of song for teaching foreign language can be one of alternative in teaching vocabulary.